Keanekaragaman Anopheles Spp di Daerah Endemis Malaria Desa Siayuh (Trans) Kabupaten Kotabaru Provinsi Kalimantan Selatan - Liestiana Indriyati; Wulan Sari Rasna Sembiring; Akhmad Rosanji (Loka Litbang Kesehatan Pangandaran, 2017)
The Health Research in 2010 informed that the prevalence of Malaria in Indonesia was 0.6%, and it was the sixth highest caused of death on infectious diseases. Malaria is transmitted by Anopheles spp. About 70 species of Anopheles have been identified as vectors of Malaria in the world, 24 species exist in Indonesia. The aim of this study was to determine the suspects of mosquito vectors and the density of mosquitoes in endemic areas, so we can establish the best interventions for vector control in the location. The research was held in Siayuh (Trans) village, Bungkukan Sub District of Kotabaru Regency in February 2015. The activities are mosquito’s collection (adult and larvae), mosquito identification, environmental survey and PCR test. Mosquito’s night collection was done by indoor and outdoor human landing collection method and rest collection in wall and cattle. The result of mosquito’s collection in Siayuh (Trans) village was 8 species of Anopheles spp. The highest percentage was Anopheles tesselatus (56%) followed by An. vagus (14%), An. kochi (11%) and An. hyrcanus group (9%). Diverse species, abundance and high density of mosquitoes in Siayuh (Trans) village was due to the geographical conditions of the village, it surrounded by marsh and many limestone puddles as a breeding habitat of Anopheles spp. Anopheles spp were found in Siayuh (Trans) village and it tend to be zoophilic, bite and resting out of the house, especially in the cattle, it makes the activities of people around the cattle at night cause a higher risk for Malaria transmission